Sosialisasi Hak dan Kewajiban ORMAWA di Lingkungan Universitas Amikom Purwokerto - Setyaningsih, Gustin; Yunita, Ika Romadoni; Setiawan, Ito (Universitas Pahlawan Tuanku Tambusai, 2024)
UKM and HMPS will reorganize or change management every year. Every administrator is obliged to know ORMAWA's rights and obligations, but in reality there are still many who do not understand. This is very visible in the work programs of the same SMEs continuously from year to year. Lack of time during the management period will have many impacts, one of which is that many administrators do not know the rights and obligations of UKM and HMPS. The campus disburses a budget of hundreds of millions of rupiah each year to UKM and HMPS to help the campus achieve the organization's vision and mission, but the results need to be evaluated. There are several ORMAWA who actually question campus policies in the wrong way. The aim of this socialization is to provide understanding to UKM and HMPS administrators about their rights and obligations. The methods used are lectures and discussions. The result of this socialization is increased understanding of UKM and HMPS administrators regarding their rights and obligations as ORMAWA administrators